A hub of high quality PhD education across Switzerland: SSPH+ Inter-university Graduate Campus. (30th September 2020) - Walser, A; Bauwens, J; Abel, T; Nocera, S; Flahault, A; Crivelli, L; Künzli, N
Abstract: Background: Due to the lack of critical masses, no Swiss university offers a full PhD education in public health sciences. Separate programs are inefficient and limit students' access to multi-disciplinary exchange. To address these problems, the Swiss School of Public Health (SSPH+) launched the Inter-university Graduate Campus (IGC) as a hub of high quality inter-disciplinary training offered across Switzerland. The SSPH+ Foundation, initiated by six universities (2005), meanwhile assembles 12 Swiss universities to represent the virtual inter-university multi-disciplinary faculty of > 250 public health science professors and their research teams. Objectives: The IGC provides PhD students state-of-the art training and access to inter-disciplinary research, teaching and networking with SSPH+ scientists throughout the country. The IGC Academic Board with representatives of 12 universities defines study recommendations and the course program. IGC meetings strengthen the inter-university exchange among students and supervisors. The SSPH+ IGC Internship Program widens career tracks in non-academic institutions. Results: Currently 298 PhD students (190 women, 108 men) enrolled in 7 partner universities and from 74 countries are part of the IGC. IGC includes courses in methods, public health science topics, and soft skills, taught by international experts. The Academic Board and student representatives are working on study recommendations, and a challenging state-of-the-art course program. The IGC coordinator leads the quality assurance which includes standardized evaluation procedures of all courses. Conclusions: The IGC is a remarkable nationwide collaboration across language regions, universities, and disciplinary borders in a country where single universities lack resources for multi-disciplinary PhD-trainings in public health sciences. Swiss as well as international PhD students enrolled in the IGC and their supervisors benefit from this unique training innovation. Key messages: The SSPH+ Inter-university Graduate Campus, as a Swiss hub of high quality teaching in public health sciences for PhD students, is an innovative and contemporary approach for small countries. Students benefit from an excellent inter-university and inter-disciplinary public health education, an international network and an easy access to innovative, comprehensive, up-to-date teaching.